High-Efficiency Mono-Cyclopentadienyl Titanium and Rare-Earth Metal Catalysts for the Production of Syndiotactic Polystyrene - Bo Wen; Hongfan Hu; Di Kang; Chenggong Sang; Guoliang Mao; Shixuan Xin (Molecules, 2023)
Syndiotactic polystyrene (SPS) refers to a type of thermoplastic material with phenyl substituents that are alternately chirally attached on both sides of an aliphatic macromolecular main chain. Owing to its excellent physical and mechanical properties, as well as its chemical stability, high transparency, and electrical insulation characteristics, SPS is used in a wide variety of technical fields. SPS is commonly produced via the stereoselective transition metal-catalyzed coordination polymerization method mediated by stereospecific catalysts, which consists of anionic mono-cyclopentadienyl derivative η5-coordinated single active metal centers (referred to as “mono-Cp’-M”), with active center metals involving Group 4 transition metals (with an emphasis on titanium) and rare-earth (RE) metals of the periodic table. In this context, the use of mono-cyclopentadienyl titanocene (mono-Cp’Ti) catalysts and mono-cyclopentadienyl rare-earth metal (mono-Cp’RE) metallocene catalysts for the syndiospecific polymerization of styrene is discussed. The effects of the mono-cyclopentadienyl ligand structure, cationic active metal types, and cocatalysts on the activity and syndiospecificity of mono-Cp’ metallocene catalysts are briefly surveyed.